Peningkatan Kemampuan Pustakawan dan Pemuda Kampung Sialang Sakti Melalui Pelatihan Pengolahan Limbah - Triono Dul Hakim; Syahdan Syahdan; Azlin Atika Putri (Fakultas Ilmu Budaya Universitas Lancang Kuning, 2021)
This service activity aims to provide training on the use of economic value waste to librarians and youth of Siak Sakti village, Siak. This is a continuation of the previous program that has been running, namely screen printing training to provide an alternative source of income for the youth of Sialang Sakti village who have several limitations so that they cannot continue their education to college due to economic factors. Therefore, it is necessary to make efforts to maximize the potential of the area, for example the village library. Sialang Sakti Village already has a Bina Ilmu village library which has been trusted as an inclusive library so that it has the opportunity to empower the community around the village. The target of this activity is to provide skills for librarians to process waste to add to the aesthetics of the library space and advanced screen printing training to the youth of Sialang Sakti village. The output produced is that librarians are able to process various wastes to improve the aesthetic appearance of the library space and the skills of youth to create a creative economy that is being developed by the Government of the Republic of Indonesia. This activity is a collaboration between a team of service lecturers who have expertise in the use of waste-based learning media and experts in screen printing.